Pemberdayaan Masyarakat Berbasis Laboratorium Medis Melalui Penyuluhan dan Skrining Kesehatan Di Dusun Kandanggajah - Doni Setiawan; Aldi Febrianysah; Annisa Nur Haliza; Firdaus Nur Rohman; Hilmi Dian Hilmawan; Levi Ayu Ramadhanty; Maya Rismayanti; Melsa Apriyanti; Nuraisyah Kurniawan; Tinia Lisnawati; Yesha Kurnia Nova; Zahra Qurratul’Ain (Jurnal Bina Pengabdian Kepada Masyarakat, 2026)
Dusun Kandanggajah, Dewasari Village, faces a complex array of public health challenges, including cases of acute respiratory infections (ARI), hypertension among the elderly, dermatitis, and dengue hemorrhagic fever (DHF), all of which are compounded by low health literacy and suboptimal environmental sanitation. These conditions formed the basis for the implementation of the Praktik Pembangunan Kesehatan Masyarakat (PPKM) program conducted from December 19–23, 2024. The methods employed included interactive health education sessions with pre- and post-test evaluations, blood pressure measurements, and routine blood examinations. The results demonstrated a statistically meaningful improvement in knowledge across all educational topics covered. Clinical laboratory-based examinations revealed that 37.5% of participants were identified with hypertension, while 13.6% were at risk of anemia. This PPKM initiative confirms that an integrated approach combining community-based health education with clinical laboratory screening is effective in simultaneously enhancing health knowledge and detecting underlying health problems. Accordingly, strengthening local health cadres and establishing continuous monitoring at the Handapherang Primary Health Center (Puskesmas) are strongly recommended as essential follow-up measures